Profitability as the Moderator of the Effects of Dividend Policy, Firm Size, and Asset Structure on Debt Policy - UMBARWATI, UMI; Fachrurrozie, Fachrurrozie (Universitas Negeri Semarang, 2018)
The purpose of this study is to examine the profitability in moderating the effect of dividend policy, firm size, and assets structure towards debt policy. The population of this study were manufacturing companies were listed on the Indonesia Stock Exchange (BEI) during 2014-2016. The population of this study were 136 companies and research samples of 37 companies. The sample selection used in this study was a purposive sampling technique obtained by 111 analysis units. Data collection techniques used are documentation techniques by collecting the required data from the financial statements. The analytical technique using moderation regression analysis using the difference absolute value test. Assets structure has a positive effect on debt policy, firm size negatively affect on debt policy and dividend policy does not significantly effect on debt policy. Profitability can be used to moderate the effect of dividend on debt policy. However, profitability can not be used to moderate firm size and assets structure towards debt policy. The conclusion of this research is that debt policy is effect by assets structure and profitability can moderate the effect of dividend policy towards debt policy.